The expression of PD-L1 protein as a prognostic factor in lung squamous cell carcinoma. (February 2017) - Takada, Kazuki; Okamoto, Tatsuro; Toyokawa, Gouji; Kozuma, Yuka; Matsubara, Taichi; Haratake, Naoki; Akamine, Takaki; Takamori, Shinkichi; Katsura, Masakazu; Shoji, Fumihiro; Oda, Yoshinao; Maehara, Yoshihiko
Highlights: The significance of PD-L1 expression in SCC patients remains unclear. The expression was evaluated with four different cut-off values in this study. The expression was associated with a poor prognosis only at the 1% cut-off value. The Ki-67 labeling index was higher in the PD-L1-positive patients than in the PD-L1-negative patients. The 1% cut-off value might become a better predictive marker than others. Abstract: Background: Programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) pathway-targeted immunotherapy has become the standard option of care in the management of lung cancer. The expression of the PD-L1 protein in lung cancer is expected to be a prognostic factor or to predict the response to PD-1-blocking antibodies. However, the association between PD-L1 positivity and the clinicopathological features and patient outcomes in lung squamous cell carcinoma (SCC) remains unclear because the definitive cut-off value for the expression of PD-L1 protein remains to be established. Materials and methods: The expression of PD-L1 protein in 205 surgically resected primary lung SCC patients was evaluated by immunohistochemistry with the antibody clone SP142. We generated a histogram to show the proportion of PD-L1-positive carcinoma cells, and set the cut-off values as 1%, 5%, 10% and 50%. Moreover, we examined the proliferative capacity of these tumors using Ki-67 immunohistochemistry. Results: The samples from 106 (51.7%), 72 (35.1%), 61 (29.7%) and 37 (18.0%) patients were positive for the expression of PD-L1 protein at cut-off values of 1%, 5%, 10% and 50%, respectively. Fisher's exact test showed that, for almost all of the factors, PD-L1 positivity was not associated with the clinicopathological features with any of the four cut-off values. Univariate and multivariate survival analyses revealed that the PD-L1-positive patients only had a poorer prognosis than the PD-L1-negative patients at the 1% cut-off value. The Ki-67 labeling index in the PD-L1-positive patients was higher than that in the PD-L1-negative patients. Conclusions: The expression of PD-L1 protein was associated with a poor prognosis in lung SCC patients. The 1% cut-off value for PD-L1 might become a better predictive marker than the other cut-off values.